Labor Transitions between Formal and Informal Employment in Egypt - Mahmoud Al-Barrawi, Alaa (AUC Knowledge Fountain, 2022)
Informal employment is the hallmark of developing economies. Egypt is no exception to this trend. Those who are informally employed are exceptionally vulnerable as they lack social protection. Moreover, large informal sectors are symptomatic of underdevelopment and have negative repercussions on the economy. Few studies examine the determinants of labor market transitions in Egypt with a focus on transitions between formal and informal labor market states. This study focuses on determinants of labor market transitions in Egypt, relying on the Egyptian Labor Market Panel Surveys of 2012 and 2018. It develops four multinomial logistic regression models to achieve this goal. The main independent variables examined are education, gender, age group, father’s level of education (a proxy for social class), and area of residence. The findings reveal the immobility of Egyptian women in the labor market except if they are moving to unemployment or inactivity. The youth seem to be particularly vulnerable as they are less likely to transition from informal to formal salaried employment. Moreover, self-employment is less accessible to the youth (hence they are less likely to transition to it), and youth in self-employment are less likely to remain/succeed there. This effectively means the youth are trapped in informal salaried employment. Moreover, educational attainment increases the odds of transition towards formal salaried employment and reduces flows out of it. The study also finds that non-employed, highly educated individuals are queuing in non-employment until they can find a position in formal salaried employment.